The redesign of amoxicillin capsules as a tablet dosage form using direct compression - Salem Elgahmi; Nawal Alrishei; Rabeaa Algaraboly; Aisha Altrablesy; Idris El-Mahdi (Libyan International Medical University Journal)
Introduction: Solid dosage forms are the most commonly used dosage form for drug delivery, and tablets are more popular than capsules because of its lower production cost, minimal potential of content tampering, and the large number of designs of tablets for various applications. Aims: The aim of this work is to redesign amoxicillin hard gelatin capsules (HGCs), commonly filled into HGCs, into tablet dosage form by employing preformulation principles. Materials and Methods: Amoxicillin capsules were obtained from the local market for this purpose. Experiments included studies on flowability and effect of compression force, followed by addition of excipients, production of tablets by direct compression, and evaluation employing standard methods of friability, hardness, disintegration, dissolution, and simulation of release kinetics. Results: The flowability of powder was estimated using Carr's index, Hausner ratio, angle of repose, and bulk density. The flowability was found poor for amoxicillin alone or with starch but improved with talc. Compression force was found to be a significant factor on friability, hardness, and disintegration. The disintegration time was rapid in case of tablets containing starch compared to amoxicillin powder compressed alone. It was essential to include small amounts of disintegrant and a lubricant to optimize tablet properties. Dissolution rates for the prepared tablets were found to be acceptable, while some formulations showed a slow release profiles corresponding to their slow disintegration. Release kinetics was found to follow both the zero-order and matrix models. Conclusion: Amoxicillin capsules can be modified to a tablet dosage form with simple handling of preformulation properties.